2018
DOI: 10.1177/2292550317749535
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Plain Film, Ultrasonography, and Computed Tomography in Nasal Bone Fractures: A Systematic Review

Abstract: Le rendement diagnostique des clichés sans préparation, de l'échographie et de la tomodensitométrie en cas de fractures de l'os nasal : une analyse systématique

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…11 The authors of each study mentioned that CR does not have high sensitivity in detecting nasal fractures, and that it specifically has difficulty detecting lateral nasal bone wall fractures. 8,20,[23][24][25] In our study, the sensitivity and specificity levels of CR were found to be 61.1% (95% CI: 35.8-82.7) and 69.2% (95% CI: 38.6-90.9), respectively.…”
Section: Discussionmentioning
confidence: 69%
“…11 The authors of each study mentioned that CR does not have high sensitivity in detecting nasal fractures, and that it specifically has difficulty detecting lateral nasal bone wall fractures. 8,20,[23][24][25] In our study, the sensitivity and specificity levels of CR were found to be 61.1% (95% CI: 35.8-82.7) and 69.2% (95% CI: 38.6-90.9), respectively.…”
Section: Discussionmentioning
confidence: 69%
“…Computed tomography (89.3%±3.1%) and USG (87.2%±3.3%) were significantly more sensitive than PF ( P <0.001 and P <0.001, respectively). The specificity of CT (94.2%±2.3%) was significantly higher ( P =0.001) than that of USG (87.4%±3.3%), but the specificity of USG was significantly higher ( P <0.001) than that of PF (67.8%±4.7%) 3 . Therefore, we think that CT is necessary for diagnosing NBF.…”
Section: Discussionmentioning
confidence: 82%
“…The diagnosis of an orbital fracture is challenging because its clinical presentation usually varies and the anatomy of the region is complex [ 21 23 ]. Although the capability of a conventional non-contrast CT in providing multiplanar thin slices or 3D reconstruction of facial bone with good spatial resolution and 3D images in orbital fractures [ 24 26 ] makes it the imaging method of choice or accepted as gold standard [ 27 29 ], there is a significant concern regarding the hazard of radiation, and in some emergency situations clinical state of patient may not stable enough to be transferred to CT room. Financial issues could also be a matter of concern for some patients.…”
Section: Discussionmentioning
confidence: 99%